The Role of Bawaslu Bekasi Regency in Law Enforcement on Violations of Election Crimes in 2024 - Wahyudi, Endik; Mardhiyyah, Chairunnisa (Jurnal Idea Hukum, 2024)
Simultaneous General Elections which are held every 5 (five) years create a momentum that cannot be underestimated. To achieve honest elections, election organizers with integrity are needed, election organizers consist of the KPU (General Election Commission), Bawaslu (Election Supervisory Body), and DKPP (Election Organizer Honorary Council). Bawaslu is a body formed by the government to supervise elections. The purpose of this research is to determine "The role of the Bekasi Regency General Election Supervisory Agency in General Election Criminal Violations in the Implementation of the 2024 General Election". The author identifies the problem, namely what is the role of the Election Supervisory Body in enforcing election crimes in 2024 in Bekasi Regency and what obstacles are faced by the Election Supervisory Body in carrying out its role in enforcing election crimes in 2024 in Bekasi Regency. This research method uses empirical research methods with techniques using primary data through interviews with members of the Bekasi Regency Bawaslu and secondary in the form of laws, regulations, and other literature. The results of the research show that Bawaslu Bekasi Regency has an important role, namely supervising election crimes in the form of prevention and prosecution. Bawaslu Bekasi Regency has obstacles in carrying out its role, internal obstacles namely the number of human resources which are limited by law, and external obstacles such as the general public who tend to be apathetic. The Bekasi Regency Bawaslu has been effective in handling election crimes, this is based on the completion of all reports received by the Bekasi Regency Bawaslu.